Effect of stimulation with electromagnetic fields in the regeneration of the sciatic nerve of the rat. - Reyes, Arturo; Holmgren, Bjorn (Revista Mexicana de Ingenieria Biomedica, 1991)
In the present work we investigated the effect that electromagnetic stimulation of the lower limb has on the regeneration of the sciatic nerve after a compression injury. Two groups (23 and 40 days) were formed to test the stimulation with dynamic magnetic fields (1.5 mV / cm) that were compared with two control groups (23 and 40 days) with spontaneous regeneration. Its evolution was followed by the functional index of the sciatic nerve (IFC) and the nerve conduction velocity. The IFC, which consists in the analysis of the gait of the hind legs, presented a similar evolution in all the groups, which suggests the same type of injury. The results of the driving speed showed statistically significant differences between the control group (a = 17 m / sec) and the groups treated with magnetic fields (a = 32 m / sec, p = 0.05) The results suggest that the effect of stimulation with magnetic fields may be a decrease in the retrograde degeneration that will prevent a greater decrease in the diameter of the axons or an improvement in their "maturation" rather than a direct effect on the velocity of the axons. axonal growth during regeneration.